"We can't breathe!" – A dilemma faced by Total Technologies (Pvt.) Ltd. amid oxygen cylinder crisis. Issue 1 (21st March 2022) - Tahir, Saad; Ramish, Asher; Mehmood, Talha
Abstract : Learning outcomes: This case study aims to be taught at an MBA level. Students who are majoring in the supply chain would benefit the most from this case study. This case study has elements of logistics management, supply chain management, supply chain strategies, warehouse and logistics and responsible supply chain. The learning outcome of this case study could be seen if the students identify the gaps in the real market setting and come up with strategies that would connect and/or fill the areas missing. Teaching objective 1: students should be able to identify unstable demand scenarios and learn how demand collaboration could be implemented in that setting. Teaching objective 2: students should identify how a transparent and interconnected supply chain, both upstream and downstream, can be created. Teaching objective 3: students should be able to understand the role of a responsible supply chain and to define the role and responsibility of each party. Teaching objective 4: students should be able to learn the dynamics of safety stocks, reorder points and incorporate that in warehouse management decisions. Case overview/synopsis: Based in Lahore, Pakistan, Total Technologies (Pvt.) Ltd is a company that supplies medical equipment and provides solutions in the health-care industry. This case explores the supply chain issues faced by Tallat Mehmood, who is the Managing Director of the company, during the third wave of the COVID-19 pandemic in April 2021. Oxygen cylinders have become the need of the hour as more and more patients need oxygen. The supply of medical gases across Pakistan has become a logistical issue, causing hospital reserves to be drained without timely replenishment. Increasing the number of beds in hospitals, with limited oxygen outlets, has increased the demand for oxygen cylinders. Operating under unstable demand and not being able to meet it has caused Tallat to realize that the company is out of its comfort zone and is not responding well to the environment. The company needs to redesign the supply chain as well as collaborate with the supplier and buyer to provide better levels of service. Complexity academic level: Masters level supply chain courses. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 9: Operations and logistics.